MUTU PELAYANAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI PUSKESMAS PIYUNGAN BANTUL TAHUN 2018 - Chanif Kurnia Sari; Maristha Monicha Putri (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2019)
Background : Health center are health service facilities that are required to provide quality, affordable, fair and equitable health services. Based on the overall outpatient waiting time of the Piyungan Bantul Public Health Center in Yogyakarta both from the registration stage, to the examination stage and the waiting stage of the drug each patient takes a long waiting time of more than one hour. The complaint mainly originated from general poly patients, because the number of patients in the general poly was classified as the most daily compared to other poly. Methods : this type of research is quantitative descriptive using a cross sectional study design. The study population was 4767 patients on average month with a sample of 98 patients using the slovin formula. Results : from the results of testing using the T test individually obtained the effect of tangible on patient satisfaction 0,099 < 0,05. The influence of reliability on patient satisfaction 0,000 < 0,05. The effect of responsiveness on patient satisfaction was 0,004 < 0,05. The effect of assurance on patient satisfaction 0,001 < 0,05. The influence of emphaty on patient satisfaction 0,004 < 0,05. From the test together, the results of the influence of service quality on patient satisfaction at Public Health Center Piyungan Bantul Yogyakarta 0.000 < 0,05. Conclusion : there is an influence of service quality (tangible, reliability, responsiveness, assurance, emphaty) on outpatient satisfaction at Public Health Center Piyungan Bantul Yogyakarta. Keywods : Tangible, Reliability, Responsiveness, Assurance, Emphaty.